2017
DOI: 10.3892/ol.2017.5935
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of ribonucleotide reductase subunit M1 in patients with pancreatic cancer who undergo curative resection followed by adjuvant chemotherapy with gemcitabine

Abstract: Abstract. To the best of our knowledge, the clinical implications of using ribonucleoside reductase subunit M1 (RRM1) in patients who undergo curative resection and adjuvant chemotherapy have not been established. In the present study, the clinical data from 101 consecutive patients who underwent macroscopically curative resection, and who received adjuvant gemcitabine chemotherapy for pancreatic cancer at the Kanagawa Cancer Centre (Yokohama, Kanagawa, Japan) between April 2005 and December 2014 were retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…Inhibition of RR induced by dFdCDP is the most significant mechanism for the enhancement of gemcitabine activity [20,21]. A recent meta-analysis revealed that patients with high RRM1 expression had largely poorer OS and DFS than those with low RRM1 expression [46,47], suggesting that the expression of RRM1 is an indicator of poor survival in patients with pancreatic cancer accepting gemcitabine chemotherapy [46]. Experiments confirmed that overexpression of RRM1 and RRM2 proteins of the pancreatic cancer cell line can achieve stable genetic gemcitabine resistance [48,49].…”
Section: Gemcitabine Resistance Mechanismsmentioning
confidence: 99%
“…Inhibition of RR induced by dFdCDP is the most significant mechanism for the enhancement of gemcitabine activity [20,21]. A recent meta-analysis revealed that patients with high RRM1 expression had largely poorer OS and DFS than those with low RRM1 expression [46,47], suggesting that the expression of RRM1 is an indicator of poor survival in patients with pancreatic cancer accepting gemcitabine chemotherapy [46]. Experiments confirmed that overexpression of RRM1 and RRM2 proteins of the pancreatic cancer cell line can achieve stable genetic gemcitabine resistance [48,49].…”
Section: Gemcitabine Resistance Mechanismsmentioning
confidence: 99%
“…Patients with advanced pancreatic cancer who showed high levels of RRM1 expression were shown to have a low survival rate following gemcitabine treatment, whereas patients with non‐small‐cell lung cancer and with low‐level RRM1 expression had significant benefits from gemcitabine/cisplatin neoadjuvant chemotherapy . There are several studies assessing the prognostic role of RRM1 expression in patients with pancreatic cancer treated by adjuvant chemotherapy with gemcitabine, and no consistent outcomes are reported . To provide a comprehensive assessment of the overall survival prognostic role of RRM1 expression in patients with pancreatic cancer receiving gemcitabine chemotherapy, we performed a meta‐analysis of published studies.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…The active forms of gemcitabine inhibit DNA synthesis by incorporating into the DNA chain or inhibiting RRM1 activity [8]. Gemcitabine has been widely used for the treatment of several aggressive solid tumour types, including non-small-cell lung cancer (NSCLC), bladder tumours, pancreatic tumours and nasopharyngeal carcinoma [912]. There are preclinical and clinical data indicating that high RRM1 protein levels in various cancers are associated with gemcitabine resistance [13, 14].…”
Section: Introductionmentioning
confidence: 99%